Event-Related Potentials to an English/Spanish Syllabic Contrast in Mexican 10–13-Month-Old Infants. (29th February 2012) - Rivera-Gaxiola, Maritza; Garcia-Sierra, Adrian; Lara-Ayala, Lourdes; Cadena, Cesar; Jackson-Maldonado, Donna; Kuhl, Patricia K.
Abstract : We report brain electrophysiological responses from 10- to 13-month-old Mexican infants while listening to native and foreign CV-syllable contrasts differing in Voice Onset Time (VOT). All infants showed normal auditory event-related potential (ERP) components. Our analyses showed ERP evidence that Mexican infants are capable of discriminating their native sounds as well as the acoustically salient (aspiration) foreign contrast. The study showed that experience with native language influences VOT perception in Spanish learning infants. The acoustic salience of aspiration is perceived by both Spanish and English learning infants, but exposure provides additional phonetic status to this native-language feature for English learning infants. The effects of early experience and neural commitment as well as the impact of acoustic salience are further discussed.